SIGNIFICANCE OF SEMICONDUCTORS IN MODERN USE - Adilova , Xalida Shamshetdin qızı; Akimbaev, Ruslan Farxodovich (Educational Research in Universal Sciences, 2023)
This article deals with the importance of semiconductors and its in the modern world.